PHYLOGENETIC AND ANTIGENIC STRUCTURE OF AVIAN INFLUENZA VIRUS OF H5N1 SUBTYPE ISOLATED FROM WATERFOWLS - Susanti, R; Damajanti Soejoedono, Retno; Kade Mahardika, I Gusti Ngurah; Wibawan, I Wayan Teguh; Thenawidjaja Suhartono, Maggy (Jurnal Veteriner, 2008)
A study was carried (1) to analyze the phylogenetic relationship of fragment hemaglutinin (HA) geneof avian influenza viruses (AIV) subtype H5N1 isolated from apparently healthy backyard waterfowls inWest Java with representative of animal and human isolates from Indonesia and some countries in Asia;(2) to find out cross-reactivity of those viruses with a standard Indonesian strain. Nucleotide sequences ofHA gene of AIV H5N1 from backyard waterfowls along with other H5N1 isolates of Indonesian and Asianorigin were aligned using with ClustalW of MEGA 3.1 program. Estimation of genetic distance and theconstruction phylogenetic tree were conducted by Neighbor Joining method and calculation of distancematrix using Kimura 2-parameter. Antigenic analysis was conducted using hemagglutination inhibition(HI) test. Result of phylogenetic analysis indicated that all viruses from backyard waterfowls form threedistinct sublineages. One lineage was located in Indonesia cluster and two lineages in Asia cluster. In thephylogenetic analysis, it was concluded that multiple introductions of AIV H5N1 to Indonesia have occurred.Six AI H5N1 viruses from backyard waterfowls (IPB1-RS to IPB6-RS) appeared to be different ancestorsthose isolated previously in Indonesia. Cross-antigenic analysis showed that nine viruses isolates used inthis study were antigenically different to Legok 2003 chicken strain of AIV H5N1. The HI titer of anti-Legok 2003 antibody with all newly isolated viruses is up to 6 log lower then the HI titer using homologstrain.
Keywords: phylogenetic, antigenic, avian influenza viruses H5N1, waterfowls